Perlindungan Hukum Bagi Pekerja Perempuan Di Indonesia - Sri Hartaty (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
The implementation of legal protection for female workers under Indonesian positive law is regulated through various national and international legal instruments. Normatively, such protection includes: (a) Law No. 13 of 2003 on Manpower; (b) Minister of Manpower Decree No. 224 of 2003, together with company regulations or collective labor agreements; (c) international provisions established by the International Labour Organization (ILO); and (d) Minister of Manpower and Transmigration Decree No. KEP-226/MEN/2000 on Minimum Wages. Within this framework, companies are obliged to provide facilities for addressing grievances or complaints submitted by female workers as a form of legal protection. The grievance resolution process must be conducted hierarchically and progressively before being referred to a counseling team. In the event of an industrial relations dispute, the initial stage of resolution must be carried out through deliberation to achieve consensus. If deliberation fails, the parties may pursue legal remedies as stipulated in Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes. This law establishes two mechanisms of dispute resolution: (1) non-litigation, which includes mediation, conciliation, and arbitration; and (2) litigation, through the Industrial Relations Court. Consequently, when disputes between employers and workers can no longer be resolved through deliberation, settlement may be pursued through judicial mechanisms to ensure legal certainty and the protection of female workers’ rights.